River boy : the story of Mark Twain - Anderson, William, 1952-; Andreasen, Dan ([New York] : HarperCollins, 2003)
Presents a picture book account of the life of Samuel Clemens, describing the childhood and youthful adventures that later shaped his writings when he grew up to become the famous author Mark Twain.
Publisher's Weekly
Bulletin (Center for Children's books)
5.2
3-6
Keywords: Twain, Mark, -- 1835-1910 -- Childhood and youth -- Juvenile literature; Authors, American -- 19th century -- Biography -- Juvenile literature; Pilots and pilotage -- Mississippi River -- Biography -- Juvenile literature; River life -- Mississippi River -- Juvenile literature; Mississippi River -- Juvenile literature; Twain, Mark, -- 1835-1910.; Authors, American; Twain, Mark, -- 1835-1910.; American authors -- Biography